2006
DOI: 10.1109/tac.2006.872760
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Synchronization of an Uncertain Complex Dynamical Network

Abstract: Abstract-This brief paper further investigates the locally and globally adaptive synchronization of an uncertain complex dynamical network. Several network synchronization criteria are deduced. Especially, our hypotheses and designed adaptive controllers for network synchronization are rather simple in form. It is very useful for future practical engineering design. Moreover, numerical simulations are also given to show the effectiveness of our synchronization approaches.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
330
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 631 publications
(334 citation statements)
references
References 19 publications
3
330
0
1
Order By: Relevance
“…[5][6][7][8][9][10][11][12] In particular, adaptive techniques, have emerged as an exciting research topic in nonlinear system control, and have been demonstrated to be an effective way to synchronize a complex network. [8][9][10] However, it is assumed that all the nodes need to be controlled. In view of impracticality of controlling all the nodes in a large-scale network, pinning control has been introduced in recent years.…”
Section: X In ͑T͒͒mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] In particular, adaptive techniques, have emerged as an exciting research topic in nonlinear system control, and have been demonstrated to be an effective way to synchronize a complex network. [8][9][10] However, it is assumed that all the nodes need to be controlled. In view of impracticality of controlling all the nodes in a large-scale network, pinning control has been introduced in recent years.…”
Section: X In ͑T͒͒mentioning
confidence: 99%
“…Chen and Zhou [10] studied synchronization of general complex networks via the adaptive feedback control scheme. Zhou, Lu and Lü [11] investigated locally and globally adaptive synchronization of an uncertain complex dynamical network. For other relevant results, we refer the readers to Refs.…”
mentioning
confidence: 99%
“…During the past few years, complex networks have become an interesting research topic and appeal to have more attention in different fields from mathematics, biology, engineering sciences (Osborn 2010;Kamel and Xia 2009;Zhang et al 2013e, 2014bWatts and Strogatz 1998;Barabasi and Albert 1999;Zhou et al 2006;Strogatz 2001;Lü and Chen 2005). A complex network is a large set of interconnected nodes, where the nodes and connections can be anything, examples are internet, transportation networks, coupled biological and chemical engineering systems, neural networks in human brains and so on.…”
Section: Introductionmentioning
confidence: 99%